Clinic in situations of sexual abuse: conceptual aspects and interdisciplinary work - Drezett, Jefferson; Pedroso, Daniela; Meirelles, Alcina de Cássia; Gebrim, Luiz Henrique (O Mundo da Saúde, 2012)
Sexual violence is taken to be a serious violation of human rights and an important problem of public health, representing the extreme restriction of sexual and reproductive autonomy of women. It is a universal increasing phenomenon and a high prevalence in the population. Though it could compromise persons of both sexes and all ages, evidences point that sexual violence affects preponderantly women, particularly the youngest and vulnerable. The objective of this article is to describe the experience of a service of reference for caring people in situations of violence, with an emphasis in the organization of actions and the role of professionals of psychology in interdisciplinary care.